The Neolithic of Mainland Scotland - Brophy, Kenneth (Edinburgh University Press, 2013)
Archaeologists show us how the Neolithic human lived in mainland Scotland, with new research, first publication of key datasets and radical reinterpretation of both burial practices and ceramics across 3rd millennium BC mainland Scotland.